Влияние добавок-электролитов на физико-механические свойства портландцемента - Шабанова, Галина Николаевна; Шумейко, Вита Николаевна; Литвинов, Дмитрий Александрович (НТУ "ХПИ", 2015)
Исследованы физико-механические свойства цементного камня с применением казеина и тиосульфата натрия в качестве добавок к портландцементу. Приведены экспериментальные данные и установлено оптимальное содержание использования указанных добавок, повышающие свойства портландцемента. Показано, что при использовании тиосульфата натрия цементный камень имел повышенные показатели прочности при сжатии. Применение казеина дает возможность использования его в качестве пластифицирующей добавки, которая существенно понижает водоцементное отношение, расширяет интервал технологической пригодности и обеспечивает удобоукладываемость цементсодержащей композиции.

Studies concerning estimation of compatibility of additives-electrolytes with Portland cement as well as efficiency of their application were carried out. Physical and mechanical properties of cement stone with the use of casein and sodium thiosulfate as additives to Portland cement were investigated. Studying Portland cement containing above mentioned additives it is determined that normal consistency of cement past is achieved with reduced water-cement ratio. Experimental data are presented and optimum content for application of given additives improving the Portland cement properties has been ascertained. It is shown that by using the sodium thiosulfate the cement stone was characterized with increased compressive strength. Acceleration of hardening processes to 7 days of curing is observed and a significant increase of strength to 28 days is provided in the presence of small quantities of sodium thiosulfate in Portland cement composition. Besides strength is increased in early stages of hardening due to rising the additive concentration. Casein application permits to use one as a plasticizer which reduces significantly the water-cement ratio, expands the range of technological serviceability, and provides placeability of cementations composition.
Influence of additives-electrolytes on physical and mechanical properties of Portland cement
Keywords: прочность; схватывание; отношение водоцементное; strength; setting time; water-cement ratio